Lithium-supplementing composite additive, lithium-supplementing positive pole piece for inhibiting flatulence and application of lithium-supplementing positive pole piece

By using lithium hydroxycycloenone lithium salt or composite additives of lithium carboxylate and aminated alumina on the positive electrode of lithium battery, the gas inflation problem during lithium battery replenishment is solved, the cycle stability and energy density of the battery are improved, and the battery is enhanced, and the security.

CN119208609APending Publication Date: 2024-12-27ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411342221.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing lithium batteries have gas bloating problems during lithium replenishment, resulting in battery capacity attenuation and safety hazards. The absorption effect of the existing technology is not ideal, especially the absorption effect of carbon dioxide is insufficient.

Method used

Using lithium-enhancing composite additives, a mixture of hydroxycycloenone lithium salt or lithium carboxylate and aminolated alumina is formed by physical or chemical modification treatment to form aminolated alumina with high specific surface area and rich pore structure as a function The coating is applied to the positive electrode sheet, and a conductive adhesive is combined to inhibit bloating.

Benefits of technology

It effectively reduces the gas bloating phenomenon during the battery circulation process, improves the cycle stability and energy density of the battery, reduces the damage to the negative electrode SEI film by hydrofluoric acid, and enhances the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208609A_ABST
    Figure CN119208609A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-supplementing composite additive, a lithium-supplementing positive pole piece for inhibiting flatulence and application, and belongs to the field of lithium ion batteries. The lithium supplementing composite additive is a mixture of a lithium supplementing agent and aminated aluminum oxide, the mass ratio of the lithium supplement agent to the aminated aluminum oxide is (6-10): (3-5); the aminated aluminum oxide is activated aluminum oxide modified by an amino organic matter; the mass ratio of the amino organic matter to the activated aluminum oxide is 3: (7-12); the lithium supplement agent is hydroxyl cycloenone dilithium salt or lithium carboxylate. The lithium-supplementing positive pole piece capable of inhibiting flatulence comprises a current collector, an active coating and a functional coating located on the surface of the active coating, and the functional coating contains a lithium-supplementing composite additive and has the functions of supplementing lithium, absorbing acid and inhibiting flatulence. The method is characterized in that the aminated alumina matrix can absorb hydrofluoric acid in an electrolyte, and the aminated group can absorb carbon dioxide generated by decomposition of a lithium supplement agent. The method can reduce the problem of battery cycle gas expansion in the use process of the lithium supplement agent, and improves the battery cycle and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium-supplementing composite additive, a lithium-supplementing positive electrode sheet capable of inhibiting flatulence, and applications thereof. Background Art

[0002] With the advancement of science and technology, new energy vehicles, energy storage power stations, etc. have developed rapidly. The application end has put forward higher requirements on the performance of lithium batteries. The improvement of battery energy density has become a hot issue in the technical research of material factories and battery factories. Since the SEI film is formed on the negative electrode surface during the formation of lithium-ion batteries, the loss of active lithium causes unnecessary loss of battery energy density. Therefore, lithium supplementation technology has also become a research hotspot for improving battery energy density.

[0003] Compared with negative electrode lithium replenishment, positive electrode lithium replenishment mainly involves adding lithium-rich additives (lithium nickelate, lithium ferrite, lithium oxalate, etc.) to the positive electrode slurry, which is highly compatible with existing production processes and has faster industrial application. Lithium carboxylate salts (such as lithium oxalate Li2C2O4) or lithium carbon oxide salts (such as lithium squarate Li2C4O4) positive electrode lithium replenishers have attracted widespread attention due to their advantages such as stability in the air, non-absorption of water, and decomposition to produce carbon dioxide without residue. However, there are many problems with lithium replenishers at present, such as incomplete decomposition of lithium replenishers, and continued decomposition during the cycle to produce gas, which causes the battery to swell, resulting in capacity decay, and in severe cases, causing the battery to swell. CN 114335420 A reports a high-safety lithium replenishment positive electrode plate. The patent is provided with a lithium replenishment layer on the surface of the current collector, which cuts off electron transfer when the battery is thermally runaway to improve the safety performance of the battery. Patent CN115548476 A reports a method for preparing a positive electrode plate, in which ferrous salt and aluminosilicate additives are added to the positive electrode to absorb oxygen and acidic substances generated by Li2NiO2 and Li5FeO4. This method has a good effect. Although aluminosilicate can absorb carbon dioxide, it is a solid insoluble substance and is poorly dispersed in the plate, so its carbon dioxide absorption effect is not ideal; CN 114583282A reports an electrolyte for absorbing CO2 in lithium oxalate lithium supplements. This patent uses a PC-based electrolyte to absorb CO2, but when the PC content is too high, it will induce the co-embedding of Li-PC solvated ions into graphite, so its application is subject to certain restrictions. Summary of the invention

[0004] The object of the present invention is to provide a lithium-supplementing composite additive, a lithium-supplementing positive electrode plate for inhibiting flatulence, and applications thereof. The anti-flatulence positive electrode plate contains a lithium-supplementing composite additive, and the lithium-supplementing composite additive has the functions of replenishing lithium, absorbing acid, and absorbing air, thereby reducing the flatulence phenomenon during the cycle of the battery cell, reducing safety hazards, and eliminating the damage of hydrofluoric acid to the negative electrode SEI film.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows: A lithium supplement composite additive, the lithium supplement composite additive is a mixture of a lithium supplement agent and amino alumina; the mass ratio of the lithium supplement agent to the amino alumina is (6-10): (3-5); the amino alumina is an activated alumina modified by amino organic matter; the mass ratio of the alumina to the amino organic matter in the impregnation process is 3: (7-12); the lithium supplement agent is a hydroxycycloenone lithium salt or a lithium carboxylate; The hydroxycycloalkenone lithium salt is Li2C3O3, Li2C4O4, Li2C5O5 or Li2C6O6; the lithium carboxylate is Li2C2O4, Li2C3O5 or Li2C4O6.

[0006] The amino organic modified activated alumina is physically modified or chemically modified; the concentration of the amino organic solution in the physical modification is 50-150 g / L; the activated alumina immersion temperature is 20-30° C., and the immersion time is 6-12 hours; the drying temperature is 80-100° C., and the drying time is 6-10 hours. The solvent of the amino organic solution is ethanol, methanol, n-propanol or n-butanol; Activated alumina is γ-Al2O3, with a specific surface area of ​​200-300m 2 / g, average pore diameter 3-15nm, pore volume 0.4-1.0cm 3 / g.

[0007] The amino organic compound in the physical modification is polyethylene polyamine, polyethylene imine or triethanolamine; wherein the polyethylene polyamine is preferably diethylene diamine, diethylene triamine, triethylene diamine, triethylene triamine, tetraethylene pentamine or tetraethylene tetraamine; The amino organic compound in the physical modification is polyethylene polyamine, polyethylene imine or triethanolamine; the amino organic compound in the chemical modification is an aminosilane coupling agent represented by the general formula (I): Wherein R is a C1-C2 alkyl group, R' is a C1-C3 alkyl group, hydrogen or a C1-C3 alkyl primary amine; and m is 1-3.

[0008] The aminosilane coupling agent is aminopropyltriethoxysilane, aminopropyltrimethoxysilane or N-aminoethyl-3-aminopropyltriethoxysilane.

[0009] The aminosilane coupling agent is chemically grafted into the alumina matrix, and the mass ratio of the alumina to the aminosilane coupling is 3:(7-12); the solvent for the chemical grafting is a mixed solution of ethanol and water; the system pH of the chemical grafting reaction is 8-10, the reaction temperature is 60-80°C, and the reaction time is 30-60min.

[0010] A flatulence-inhibiting lithium-supplementing positive electrode sheet, the positive electrode sheet comprising a current collector, an active coating coated on the current collector, and a functional coating coated on the surface of the active coating; the functional coating comprises the above-mentioned lithium-supplementing composite additive and a conductive adhesive.

[0011] The current collector is a conventional aluminum foil, a composite aluminum foil or a perforated aluminum foil; the active coating comprises an active substance, a conductive agent and a binder; the active substance is one of lithium cobalt oxide, lithium-rich lithium manganese oxide, nickel cobalt lithium manganese oxide, lithium manganese oxide and lithium iron manganese phosphate; the conductive agent is one of superconducting carbon black, carbon nanotubes and carbon fibers; the binder is one of polytetrafluoroethylene, polyvinylidene fluoride and polyacrylic acid amide; the conductive binder in the functional coating is a polyimide-carbon nanotube composite conductive binder ZONE80.

[0012] The active material accounts for 92% to 96% of the total solid mass of the active material, the conductive agent and the binder, and the surface density of the active coating is 100 to 280 g / m 2 The lithium-supplementing composite additive accounts for 90wt% to 95wt% of the functional coating, and the surface density of the functional coating is 3 to 23g / m 2 .

[0013] The lithium-supplementing composite additive or the lithium-supplementing positive electrode plate for inhibiting flatulence is used in a lithium battery. The lithium battery structure also includes a negative electrode plate, a separator and an electrolyte.

[0014] The present invention has the following beneficial effects: 1. The lithium-replenishing composite additive of the present invention is a mixture of a lithium-replenishing agent (hydroxycycloenone lithium salt and lithium carboxylate) and amide alumina; the lithium-replenishing agent of the present invention has a high theoretical charge specific capacity, and the decomposition products of the electrochemical reaction are mainly carbon dioxide gas and carbon, and will not introduce impurities that interfere with the electrochemical reaction of the system, and is a very ideal positive electrode pre-lithiation reagent; amide alumina can reduce the expansion problem of the lithium-replenishing agent caused by incomplete decomposition during battery use.

[0015] 2. The amino alumina in the present invention has a rich pore structure and a large specific surface area. Grafting or loading amino groups onto the alumina matrix can provide more alkaline reaction active sites, have a better effect of absorbing carbon dioxide acid gas, reduce the side effects caused by the use of lithium supplements, and reduce the risk of bulging and flatulence during battery cycling.

[0016] 3. In addition, the solute of current lithium-ion electrolytes is usually LiPF6 dissolved in carbonate solvents. LiPF6 itself is unstable and easily ionizes to form LiF and PF5. The electrolyte usually contains more or less impure water, which will cause LiPF6 to hydrolyze and produce HF; the produced PF5 is a strong Lewis acid, which easily catalyzes the decomposition of carbonates, leading to a series of side reactions and ultimately the accumulation of HF acid. The inorganic alumina matrix can react with acidic substances such as hydrofluoric acid generated during battery use, reducing the damage of acidic substances to the negative electrode SEI film; improving the safety and cycle stability of the battery.

[0017] 4. The lithium-supplementing composite additive is coated on the surface of the positive electrode as a positive electrode pre-lithiation material. It is highly compatible with the existing battery preparation process and compensates for the irreversible lithium loss during the first charge and discharge process of the lithium battery, thereby improving the overall capacity of the battery. The battery using the lithium-supplementing composite additive in the present invention to prepare the positive electrode has a higher battery discharge specific capacity, which improves the battery's cycle stability and energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet of the present invention. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Examples 1-3 and Comparative Examples 1-3 This embodiment and comparative example provide a lithium supplement composite additive, the raw material composition and the preparation method thereof are as follows: Lithium oxalate compound (Li2C2O4, hereinafter referred to as lithium oxalate) is used as lithium supplement, tetraethylenepentaamine (N1) is amino organic matter, γ-Al2O3 (A1, specific surface area 200m 2 / g, pore diameter 15nm, pore volume 0.4cm 3 / g) as the matrix, four portions of 100g of alumina were weighed according to Table 1; and the composite lithium supplement was prepared by the following method; Physical impregnation method: Example 1: 233.3 g of tetraethylene pentaamine was dissolved in ethanol to prepare an ethanol solution with a concentration of 150 g / L, and then 100 g of alumina was added to the above solution, stirred and immersed for 6 hours, and dried at 80°C for 6 hours to obtain amino-functionalized alumina; the above amino-functionalized alumina and 1111.1 g of lithium oxalate were dry-ground and mixed to obtain a composite lithium supplement SL-C1; Example 2: 300g of tetraethylene pentaamine was dissolved in ethanol to prepare an ethanol solution with a concentration of 100g / L, and then 100g of alumina was added to the above solution, stirred and immersed for 12h, and dried at 100°C for 10h to obtain amino-functionalized alumina; the above amino-functionalized alumina was dry-ground and mixed with 800g of lithium oxalate to obtain a composite lithium supplement SL-C2; Example 3: 400g of tetraethylene pentaamine was dissolved in ethanol to prepare an ethanol solution with a concentration of 50g / L, and then 100g of alumina was added to the above solution, stirred and immersed for 8h, and dried at 90°C for 8h to obtain amino-functionalized alumina; the above amino-functionalized alumina and 500g of lithium oxalate were dry-ground and mixed to obtain a composite lithium supplement SL-C3; Comparative Example 1: 100 g of aluminum oxide and 200 g of lithium oxalate were dry-ground and mixed evenly to obtain a composite lithium supplement SL-C4; Comparative Example 2: Pure lithium oxalate is named lithium supplement composite additive SL-C5; Comparative Example 3: Alumina A1 is named lithium supplement composite additive SL-C6; Embodiment 4-6 This embodiment provides a lithium supplement composite additive, and the steps of the preparation method of the lithium supplement composite additive are as follows: Lithium oxalate compound was used as lithium supplement agent, aminopropyltriethoxysilane (N2) was used as aminosilane coupling agent, γ-Al2O3 (A1, specific surface area 200m 2 / g, pore diameter 15nm, pore volume 0.4cm 3 / g) as the matrix, weigh three portions of 100g alumina according to Table 1, and weigh 233.30g, 300g, 400g of N2 aminosilane coupling agent, 1111.1g, 800g, 500g of lithium oxalate supplement respectively; prepare the composite lithium supplement by the following method; Chemical grafting method: Example 4: 233.3 g of aminopropyltriethoxysilane was dissolved in a mixture of ethanol and water in a volume ratio of 1:1, and the above coupling agent solution was gradually added to alumina, the pH was adjusted to 8, the temperature was kept at 60°C, and the reaction was carried out for 30 minutes. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-functionalized alumina by chemical grafting; the above amino-functionalized alumina and 1111.1 g of lithium oxalate were dry-ground and mixed to obtain a composite lithium supplement SL-C7; Example 5: 300 g of aminopropyltriethoxysilane was dissolved in a mixture of ethanol and water in a volume ratio of 1:1, and the above coupling agent solution was gradually added to alumina, the pH was adjusted to 8, the temperature was kept at 70°C, and the reaction was carried out for 60 minutes. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-functionalized alumina by chemical grafting; the above amino-functionalized alumina and 800 g of lithium oxalate were dry-ground and mixed to obtain a composite lithium supplement SL-C8; Example 6: 400 g of aminopropyltriethoxysilane was dissolved in a mixture of ethanol and water in a volume ratio of 1:1, and the above coupling agent solution was gradually added to alumina, the pH was adjusted to 8, the temperature was kept at 80°C, and the reaction was carried out for 40 minutes. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-functionalized alumina (amidated alumina) by chemical grafting method; the amination alumina and 500 g of lithium oxalate were dry-ground and mixed to obtain a composite lithium supplement SL-C9; Examples 7-9 and Comparative Examples 4-6 This embodiment and comparative example provide a lithium supplement composite additive, the raw material composition and the preparation method thereof are as follows: The method uses lithium squarate (Li2C4O4, hereinafter referred to as lithium squarate) as a lithium supplement, triethanolamine (N3) as an amino organic compound, and γ-Al2O3 (A2, with a specific surface area of ​​300m 2 / g, pore diameter 10nm, pore volume 0.8cm 3 / g) as the matrix, and the remaining dosage and steps are the same as those of SL-C1 to SL-C4 of Examples 1-3, and the preparation method is used to prepare SL-F1 to SL-F3 corresponding to Examples 7-9, specifically; Example 7: 233.3 g of triethanolamine (N3) was dissolved in ethanol to prepare an ethanol solution with a concentration of 150 g / L, and then 100 g of alumina (A2) was added to the above solution, stirred and impregnated for 6 hours, and dried at 80°C for 6 hours to obtain amino-functionalized alumina; the above amino-functionalized alumina and 1111.1 g of lithium squarate were dry-ground and mixed to obtain a composite lithium supplement SL-F1; Example 8: 300 g of triethanolamine (N3) was dissolved in ethanol to prepare an ethanol solution with a concentration of 100 g / L, and then 100 g of alumina (A2) was added to the above solution, stirred and immersed for 12 hours, and dried at 100° C. for 10 hours to obtain amino-functionalized alumina; the above amino-functionalized alumina was dry-ground and mixed with 800 g of lithium squarate to obtain a composite lithium supplement SL-F2; Example 9: 400 g of triethanolamine (N3) was dissolved in ethanol to prepare an ethanol solution with a concentration of 50 g / L, and then 100 g of alumina (A2) was added to the above solution, stirred and immersed for 12 hours, and dried at 100° C. for 10 hours to obtain amino-functionalized alumina; the above amino-functionalized alumina and 500 g of lithium squarate were dry-ground and mixed to obtain a composite lithium supplement SL-F3; Comparative Example 4: A mixture of lithium squarate and unmodified alumina A2 in a mass ratio of 10:5 is used as the lithium supplement composite additive SL-F4; Comparative Example 5: Pure lithium squarate is named as lithium supplement composite additive SL-F5; Comparative Example 6: Alumina A2 is named lithium supplement composite additive SL-F6; Examples 10-12 and Comparative Examples 7-8 This embodiment and comparative example provide a lithium supplement composite additive, the raw material composition and the preparation method thereof are as follows: Preparation methods of SL-F7 to SL-F9 corresponding to Examples 10-12 of lithium-supplementing composite additives and SL-F10 and SL-F11 corresponding to Comparative Examples 7-8: The method uses a lithium squarate compound as a lithium supplement, N-aminoethyl-3-aminopropyltriethoxysilane (N4) as an aminosilane coupling agent, and γ-Al2O3 (A3, specific surface area 250m 2 / g, pore diameter 10nm, pore volume 0.8cm 3 / g) as the matrix, and the remaining steps are the same as the preparation method of SL-C7 to SL-C9 of Examples 4-6 to prepare SL-F7 to SL-F9 of Examples 12-14, as follows: Example 10: 233.3 g of N-aminoethyl-3-aminopropyltriethoxysilane (N4) was placed in a mixture of ethanol and water in a volume ratio of 1:1, and the above coupling agent solution was gradually added to alumina A3, the pH was adjusted to 8, the temperature was kept at 60°C, and the reaction was carried out for 30 minutes. After the reaction was completed, the reaction was filtered, washed, and dried to obtain chemically grafted amino-functionalized alumina; the above amino-functionalized alumina and 1111.1 g of lithium squarate were dry-ground and mixed to obtain a composite lithium supplement SL-F7; Example 11: 300 g of N-aminoethyl-3-aminopropyltriethoxysilane (N4) was placed in a mixture of ethanol and water in a volume ratio of 1:1, and the above coupling agent solution was gradually added to alumina A3, the pH was adjusted to 8, the temperature was kept at 70°C, and the reaction was carried out for 30 minutes. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-functionalized alumina by chemical grafting; the above amino-functionalized alumina and 800 g of lithium squarate were dry-ground and mixed to obtain a composite lithium supplement SL-F8; Example 12: 400 g of N-aminoethyl-3-aminopropyltriethoxysilane (N4) was placed in a mixture of ethanol and water in a volume ratio of 1:1, and the above coupling agent solution was gradually added to alumina A3, the pH was adjusted to 8, the temperature was kept at 80°C, and the reaction was carried out for 30 minutes. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-functionalized alumina by chemical grafting; the above amino-functionalized alumina and 500 g of lithium squarate were dry-ground and mixed evenly to obtain a composite lithium supplement agent SL-F9; Comparative Example 7: A mixture of lithium squarate and unmodified alumina A3 in a mass ratio of 10:5 is named lithium supplement composite additive SL-F10; Comparative Example 8: Pure aluminum oxide A3 is named as lithium supplement composite additive SL-F11.

[0022] Table 1. Statistics of lithium-supplementing composite additives In the above lithium-supplementing composite additives, the content of amino alumina is SL-C1<SL-C2<SL-C3; SL-F1<SL-F2<SL-F3; SL-C7<SL-C8<SL-C9; SL-F7<SL-F8<SL-F9; SL-C4~SL-C6 and SL-F4~SL-F6, SL-F10~SL-F11 do not contain amino groups.

[0023] Application Example 1 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent superconducting carbon black, and the binder polyvinylidene fluoride are mixed in an N-methylpyrrolidone solvent (NMP) system in a weight ratio of 94:3:3, and stirred until they are uniformly mixed to obtain a positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil and dried to obtain a surface density of 200g / m 2 According to the mass ratio of 93:7, the lithium-supplementing composite additive SL-C1 (Example 1) and the conductive adhesive ZONE80M were weighed and coated on the surface of the active coating after being made into a slurry. The coating surface density was 10g / m 2 , and then rolled and cut into positive electrode sheets.

[0024] Preparation of negative electrode sheets: The negative electrode active material silicon oxide 500, the conductive agent superconducting carbon black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose are mixed in an aqueous solvent at a mass ratio of 96:1:2:1 until they are uniformly mixed to prepare a negative electrode slurry. The negative electrode slurry is coated on the negative electrode collector copper foil at an NP ratio of 1.1, dried, and rolled and die-cut to form a negative electrode sheet.

[0025] Battery assembly: The positive electrode and negative electrode are matched with a separator, and are stacked, assembled, injected, and formed to produce an application example 1 battery.

[0026] Application Example 2 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: According to the same preparation method as in Application Example 1, an active coating was prepared. The lithium supplement composite additive SL-C2 (Example 2) and the conductive adhesive ZONE80M were weighed in a mass ratio of 93:7 to prepare a functional coating slurry, which was then applied to the surface of the active coating. The coating surface density was 10 g / m 2 , and then rolled and cut into positive electrode sheets.

[0027] The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those of Application Example 1. After lamination, assembly, liquid injection, and formation, the battery of Application Example 2 is manufactured.

[0028] Application Example 3 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: According to the same preparation method as in Application Example 1, an active coating was prepared. The lithium-supplementing composite additive SL-C3 and the conductive adhesive ZONE80M in Example 3 were weighed in a mass ratio of 93:7 to prepare a functional coating slurry, which was then applied to the surface of the active coating. The coating surface density was 10 g / m 2 , and then rolled and cut into positive electrode sheets.

[0029] The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those in Application Example 1. After lamination, assembly, liquid injection, and formation, the battery of Application Example 3 is manufactured.

[0030] Comparative Application Examples 1-3 This comparative application example provides a positive electrode plate and a lithium-ion battery, and the raw material composition and method are as follows: According to the same preparation method as in Application Example 1, an active coating was prepared. The lithium-supplementing composite additive and the conductive adhesive ZONE80M of the comparative example were weighed in a mass ratio of 93:7 to prepare a functional coating slurry, which was then applied to the surface of the active coating. The coating surface density was 10 g / m 2 , and then rolled and cut into positive electrode sheets.

[0031] The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those in Application Example 1. After lamination, assembly, liquid injection, and formation, the battery of the corresponding comparative application example is manufactured.

[0032] Comparative Application Example 1: The lithium supplement composite additive is SL-C4 of Comparative Example 1; the remaining steps are the same as those of Application Example 1; Comparative Application Example 2: The lithium supplement composite additive is SL-C5 of Comparative Example 2; the remaining steps are the same as those of Application Example 1; Comparative Application Example 3: The lithium supplement composite additive is SL-C6 of Comparative Example 3; the remaining steps are the same as those of Application Example 1.

[0033] Comparative Application Example 4 This comparative application example provides a positive electrode plate and a lithium-ion battery, and the raw material composition and method are as follows: According to the same preparation method as in Application Example 1, an active coating is prepared, and there is no functional coating on the surface of the active coating, which is then rolled and cut into positive electrode sheets.

[0034] The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those in Application Example 1. After lamination, assembly, liquid injection, and formation, the battery of Comparative Application Example 4 is made.

[0035] Application Examples 4-6 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: According to the same preparation method as in Application Example 1, an active coating was prepared; The difference between the functional coating and application example 1 is that the functional coating used is a lithium-supplementing composite additive and a conductive adhesive ZONE80M weighed in a mass ratio of 93:7, and then coated on the surface of the active coating with a coating surface density of 10 g / m 2 , and then rolled and cut into positive electrode sheets.

[0036] The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those in Application Example 1. After lamination, assembly, liquid injection, and formation, batteries of Application Examples 4-6 are made.

[0037] Application Example 4: The lithium supplement composite additive is SL-C7 of Example 4; the remaining steps are the same as those of Application Example 1; Application Example 5: The lithium supplement composite additive is SL-C8 of Example 5; the remaining steps are the same as those of Application Example 1; Application Example 6: The lithium supplement composite additive is SL-C9 of Example 6; the remaining steps are the same as those of Application Example 1; Application Example 7 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: Lithium cobalt oxide (LiCoO2), conductive agent superconducting carbon black, and binder polyvinylidene fluoride were weighed according to a weight ratio of 96:2:2, and the slurry was prepared by the slurry preparation method described in Example 1 at a surface density of 280 g / m 2 The active coating was coated on the surface of the aluminum foil and dried to obtain the active coating; the lithium supplement composite additive SL-C1 and the conductive adhesive ZONE80M of Example 1 were weighed in a mass ratio of 95:5, and the slurry was coated on the surface of the active coating. The coating surface density was 23 g / m 2 , and is rolled and cut into positive electrode sheets; The negative electrode preparation method and ratio are exactly the same as those in Example 1. After lamination, assembly, liquid injection and formation, the battery of Application Example 7 is manufactured.

[0038] Application Example 8 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: According to the weight ratio of 92:4:4, lithium cobalt oxide (LiCoO2), superconducting carbon black as a conductive agent, and polyvinylidene fluoride as a binder were weighed respectively, and the slurry was prepared by the slurry preparation method described in Example 1 at a surface density of 100 g / m 2 Apply it on the surface of aluminum foil and dry it to obtain an active coating; weigh the lithium supplement composite additive SL-C1 and the conductive adhesive ZONE80M according to a mass ratio of 90:10, make a slurry and apply it on the surface of the active coating. The coating surface density is 23g / m 2 , and is made into positive electrode sheets through rolling and slitting; the negative electrode ratio, preparation method, surface density, etc. are exactly the same as those in Application Example 1, and is made into Application Example 8 battery through lamination, assembly, liquid injection, and formation.

[0039] Application Example 9 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: Lithium cobalt oxide (LiCoO2), conductive agent superconducting carbon black, and binder polyvinylidene fluoride were weighed according to a weight ratio of 96:2:2, and the positive electrode slurry was prepared by the slurry preparation method described in Example 1 with a surface density of 280 g / m 2 The active coating was coated on the surface of aluminum foil and dried; the lithium supplement composite additive SL-C7 and the conductive adhesive ZONE80M were weighed in a mass ratio of 95:5, made into a slurry and coated on the surface of the active coating, with a coating surface density of 3g / m 2 , and is rolled and cut into positive electrode sheets; The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those of Application Example 4. After lamination, assembly, liquid injection, and formation, the battery of Application Example 9 is manufactured.

[0040] Application Example 10 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: Lithium cobalt oxide (LiCoO2), superconducting carbon black as a conductive agent, and polyvinylidene fluoride as a binder were weighed in a weight ratio of 92:4:4, and the slurry was prepared by the slurry preparation method described in Example 1 at a surface density of 100 g / m 2 Apply it on the surface of aluminum foil and dry it to obtain an active coating; weigh the lithium supplement composite additive SL-C7 and the conductive adhesive ZONE80M according to a mass ratio of 90:10, make a slurry and apply it on the surface of the active coating. The coating surface density is 3g / m 2 , and is rolled and cut into positive electrode sheets; The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those of Application Example 4. After lamination, assembly, liquid injection, and formation, the battery of Application Example 10 is manufactured.

[0041] Application Example 11 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: Preparation of positive electrode sheet: The positive electrode active material ternary nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, hereinafter referred to as NCM811), conductive agent carbon nanotubes, and binder polytetrafluoroethylene are mixed in a weight ratio of 94:2:4 in an N-methylpyrrolidone solvent (NMP) system and stirred until uniformly mixed to obtain a positive electrode slurry. The positive electrode slurry is coated on a positive electrode current collector aluminum foil and dried to obtain a surface density of 200 g / m 2 According to the mass ratio of 93:7 weighed Example 7-9 lithium supplement composite additive, conductive binder ZONE80M, dispersed evenly in the solvent to form a slurry, according to the surface density of 10g / m 2 The slurry is coated on the surface of the aforementioned active coating, and is rolled and cut into positive electrode sheets.

[0042] Preparation of negative electrode sheets: negative electrode active material silica 500, conductive agent superconducting carbon black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose are mixed in a deionized water solvent system in a weight ratio of 96.0:1:1:2. After being fully stirred until uniformly mixed, a negative electrode slurry is obtained. The negative electrode slurry is coated on the negative electrode collector copper foil and dried at an NP ratio of 1.1 to form a surface density negative electrode active material layer, which is then rolled and die-cut to form a negative electrode sheet.

[0043] Battery assembly: The aforementioned positive and negative electrodes are combined with a separator, stacked, assembled, injected, and formed into the battery of Application Example 11.

[0044] Application Example 12 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: According to the weight ratio of 96:2:2, the ternary NCM811, the conductive agent carbon nanotubes, and the binder polytetrafluoroethylene were weighed respectively, and the slurry preparation method described in Application Example 11 was used to prepare the slurry according to the surface density of 280g / m 2 The active coating was coated on the surface of the aluminum foil and dried to obtain the active coating. The lithium supplement composite additive SL-F2 prepared in Example 8 and the conductive adhesive ZONE80M were weighed in a mass ratio of 95:5, dispersed evenly in a solvent to prepare a slurry, and the slurry was prepared at a surface density of 23 g / m 2 The slurry is coated on the surface of the aforementioned active coating, and is rolled and cut into positive electrode sheets; the negative electrode ratio, preparation method, surface density, etc. are exactly the same as those in Example 11, and is stacked, assembled, injected, and formed to form the battery of Application Example 12.

[0045] Application Example 13 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: According to the weight ratio of 92:4:4, the ternary NCM811, the conductive agent carbon nanotubes, and the binder polytetrafluoroethylene were weighed respectively, and the slurry preparation method described in Application Example 11 was used to prepare the slurry at a surface density of 100 g / m 2 The active coating was coated on the surface of the aluminum foil and dried; the lithium-supplementing composite additive SL-F3 and the conductive adhesive ZONE80M prepared in Example 9 were weighed in a mass ratio of 90:10, dispersed evenly in a solvent to form a slurry, and the surface density was 3 g / m 2 The slurry is coated on the surface of the aforementioned active coating, and is rolled and cut into positive electrode sheets; the negative electrode ratio, preparation method, surface density, etc. are exactly the same as those in Example 11, and is stacked, assembled, injected, and formed to form the battery of Application Example 13.

[0046] Comparative Application Examples 5-7 This comparative application example provides a positive electrode plate and a lithium-ion battery, and the raw material composition and method are as follows: Comparative Application Example 5: The SL-F4 prepared in Comparative Example 4 was used as a lithium supplement composite additive, and other positive and negative electrode ratios, preparation methods, surface densities, etc. were exactly the same as those in Application Example 11 to prepare a battery in Comparative Application Example 5.

[0047] Comparative Application Example 6: The SL-F5 prepared in Comparative Example 5 was used as a lithium supplement composite additive, and other positive and negative electrode ratios, preparation methods, surface densities, etc. were exactly the same as those in Application Example 11 to prepare a battery in Comparative Application Example 6.

[0048] Comparative Application Example 7: The SL-F6 prepared in Comparative Example 6 was used as a lithium supplement composite additive, and other positive and negative electrode ratios, preparation methods, surface densities, etc. were exactly the same as those in Application Example 11 to prepare a Comparative Application Example 7 battery.

[0049] Comparative Application Example 8 This comparative application example provides a positive electrode plate and a lithium-ion battery, and the raw material composition and method are as follows: The same active coating preparation method as in Application Example 11 was used, and the surface of the active coating had no functional coating, and the positive electrode sheet was made by rolling and slitting. The negative electrode ratio, preparation method, surface density, etc. were completely the same as in Application Example 11, and the battery of Comparative Application Example 8 was made by lamination, assembly, injection, and formation.

[0050] Application Example 14 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: Preparation of positive electrode sheet: The positive electrode active material lithium manganese iron phosphate (LiFe 0.4 Mn 0.6 PO4, hereinafter referred to as lithium iron manganese phosphate LFMP), conductive agent carbon nanotubes, and binder polyvinylidene fluoride are mixed in a weight ratio of 94:2:4 in an N-methylpyrrolidone solvent (NMP) system and stirred until uniformly mixed to obtain a positive electrode slurry. The positive electrode slurry is coated on a positive electrode current collector aluminum foil and dried to obtain a surface density of 200g / m 2 Active coating; weigh the lithium supplement composite additive SL-F7 and the conductive adhesive ZONE80M according to the mass ratio of 93:7, make a slurry and apply it on the surface of the active coating, and the coating surface density is 10g / m 2 , and then rolled and cut into positive electrode sheets.

[0051] Preparation of negative electrode sheet: negative electrode active material silica 500, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose are mixed in a deionized water solvent system in a weight ratio of 96.0:1:1:2. After being fully stirred until mixed evenly, a negative electrode slurry is obtained. The negative electrode slurry is coated on the negative electrode collector copper foil and dried at an NP ratio of 1.1 to form a surface density negative electrode active material layer, which is then rolled and die-cut to form a negative electrode sheet.

[0052] Battery assembly: The aforementioned positive and negative electrodes are combined with a separator, stacked, assembled, injected, and formed into the battery of Application Example 14.

[0053] Application Example 15 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: The positive electrode active material is lithium manganese iron phosphate (LiFe 0.4 Mn 0.6PO4, hereinafter referred to as lithium iron manganese phosphate LFMP), conductive agent carbon nanotubes, and binder polyvinylidene fluoride are weighed in a weight ratio of 96:2:2. Lithium iron manganese phosphate, conductive agent carbon nanotubes, and binder polytetrafluoroethylene are weighed respectively, and stirred in an N-methylpyrrolidone solvent (NMP) system until they are uniformly mixed to obtain a positive electrode slurry. The positive electrode slurry is coated on a positive electrode current collector aluminum foil and dried to obtain a surface density of 280g / m 2 The active coating is made of lithium-supplementing composite additive SL-F8 and conductive adhesive ZONE80M in a mass ratio of 95:5, and the slurry is applied to the surface of the active coating. The coating surface density is 23g / m 2 , and is rolled and cut into positive electrode sheets; The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those of Application Example 14. After lamination, assembly, liquid injection, and formation, the battery of Application Example 15 is manufactured.

[0054] Application Example 16 This application example provides a positive electrode sheet and a lithium-ion battery, and the raw material composition and method are as follows: According to the weight ratio of 92:4:4, lithium manganese iron phosphate, conductive agent carbon nanotubes, and binder polytetrafluoroethylene were weighed respectively, and stirred in an N-methylpyrrolidone solvent (NMP) system until they were uniformly mixed to obtain a positive electrode slurry. The positive electrode slurry was coated on the positive electrode current collector aluminum foil and dried to obtain a surface density of 100 g / m 2 Active coating; weigh the lithium supplement composite additive SL-F9, SL-F9 and conductive adhesive ZONE80M in a mass ratio of 90:10, make a slurry and apply it on the surface of the active coating, the coating surface density is 3g / m 2 , and is rolled and cut into positive electrode sheets; The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those of Application Example 14. After lamination, assembly, liquid injection, and formation, the battery of Application Example 16 is manufactured.

[0055] Comparative Application Example 9 This comparative application example provides a positive electrode plate and a lithium-ion battery, and the raw material composition and method are as follows: Lithium manganese iron phosphate is used as the main positive electrode material, SL-F10 of comparative example 7 is used as a lithium supplement composite additive, and other positive and negative electrode ratios, preparation methods, surface densities, etc. are exactly the same as those of application example 14 to make a battery of comparative application example 9.

[0056] Comparative Application Example 10 This comparative application example provides a positive electrode plate and a lithium-ion battery, and the raw material composition and method are as follows: Using the same active coating preparation method as in Application Example 14, the lithium-supplementing composite additive SL-F11 and the conductive adhesive ZONE80M of Comparative Example 8 were weighed in a mass ratio of 93:7, and the slurry was coated on the surface of the active coating. The coating surface density was 10 g / m 2 , and then rolled and cut into positive electrode sheets.

[0057] The negative electrode ratio, preparation method, surface density, etc. are exactly the same as those of Application Example 14. After lamination, assembly, liquid injection, and formation, the battery of Comparative Application Example 10 is made.

[0058] Comparative Application Example 11 This comparative application example provides a positive electrode plate and a lithium-ion battery, and the raw material composition and method are as follows: The same active coating preparation method as in Application Example 14 was used, and the surface of the active coating had no functional coating, and the positive electrode sheet was made by rolling and slitting. The negative electrode ratio, preparation method, surface density, etc. were completely the same as in Application Example 14, and the battery of Comparative Application Example 11 was made by lamination, assembly, injection, and formation.

[0059] The batteries of the above application examples and comparative application examples were subjected to 1C@25℃ cycle test, and the performance is shown in Table 2: Table 2. Parameters and battery performance of different application examples and comparative application examples As can be seen from Table 2, the functional layers in Application Examples 1 to 3 contain lithium-supplementing composite additives prepared by physical impregnation, and the amino loading gradually increases, so the capacity retention rate of 500 cycles gradually increases; the functional layers in Application Examples 4 to 6 contain lithium-supplementing composite additives prepared by chemical grafting, and the loading gradually increases, so the capacity retention rate has the same rule as that of Examples 1 to 3, that is, adding amino-containing lithium-supplementing composite additives can improve the cycle life of the battery. The lithium-supplementing composite additive in Comparative Application Example 1 does not contain amino groups, and Comparative Application Example 2 only contains lithium-supplementing agents. Both of them have flatulence problems after less than 500 cycles; Comparative Application Example 4 does not contain a functional coating, and the battery is cycled 500 times, with a capacity retention rate of 91%. Comparative Application Example 3 contains a functional coating, and the battery is cycled 500 times, with a capacity retention rate of 91.5%, which is higher than Comparative Application Example 3. Alumina can absorb hydrofluoric acid and reduce the damage of hydrofluoric acid to the negative electrode SEI film.

[0060] The same lithium-replenishing composite additive SL-C1 was added in Application Examples 1, 7 and 8, but the content in the functional coating gradually increased, so the discharge capacity retention rate became larger; the lithium-replenishing composite additive SL-C7 was added in Application Examples 4, 9 and 10, and the content of the lithium-replenishing composite additive in the functional layer gradually increased, and the discharge retention rate also showed the same rule. Compared with Application Examples 1, 7 and 8 of lithium cobalt oxide batteries, Application Examples 11 to 13 and Application Examples 14 to 16 of lithium manganese iron phosphate batteries corresponding to ternary NMC811 batteries showed the same rule. Compared with the lithium cobalt oxide batteries of comparative application examples 1 to 4, the ternary NCM811 batteries of comparative application examples 1 to 4, and the lithium iron manganese phosphate batteries of comparative application examples 9 to 11, the battery cycle performance shows the same rule, the battery containing the amino lithium supplement composite additive coating> the battery containing the aluminum oxide coating> the uncoated battery> the battery containing the lithium supplement agent without amino groups, and the lithium supplement positive electrode pieces without amino groups all have flatulence after less than 500 cycles. Therefore, the amino-containing aluminum oxide has the effect of inhibiting the cyclic flatulence of the lithium supplement positive electrode pieces.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium supplement composite additive, characterized in that: The lithium-replenishing composite additive is a mixture of a lithium-replenishing agent and amino-alumina; the mass ratio of the lithium-replenishing agent to the amino-alumina is (6-10): (3-5); the amino-alumina is an activated alumina modified by amino organic matter; the mass ratio of the amino organic matter to the activated alumina is 3: (7-12); the lithium-replenishing agent is hydroxycycloenone dilithium salt or lithium carboxylate.

2. The lithium supplement composite additive according to claim 1, characterized in that: The hydroxycycloalkenone dilithium salt is any one of Li2C3O3, Li2C4O4, Li2C5O5 and Li2C6O6; the lithium carboxylate is any one of Li2C2O4, Li2C3O5 and Li2C4O6.

3. The lithium supplement composite additive according to claim 1 or 2, characterized in that: The activated alumina is γ-Al2O3 with a specific surface area of ​​200 to 300 m 2 / g, average pore diameter 3-15nm, pore volume 0.4-1.0cm 3 / g.

4. The lithium supplement composite additive according to claim 3, characterized in that: The amino organic modified activated alumina is physically modified or chemically modified; in the physical modification, the amino organic is polyethylene polyamine, polyethylene imine or triethanolamine; in the chemical modification, the amino organic is an aminosilane coupling agent represented by the general formula (I): Wherein R is a C1-C2 alkyl group, R' is a C1-C3 alkyl group, hydrogen or a C1-C3 alkyl primary amine; and m is 1-3.

5. The lithium supplement composite additive according to claim 4, characterized in that: The aminosilane coupling agent is aminopropyltriethoxysilane, aminopropyltrimethoxysilane or N-aminoethyl-3-aminopropyltriethoxysilane.

6. A lithium-supplemented positive electrode sheet for inhibiting flatulence, characterized in that: The positive electrode plate comprises a current collector, an active coating coated on the current collector and a functional coating coated on the surface of the active coating; the functional coating comprises the lithium supplement composite additive according to any one of claims 1 to 5 and a conductive binder.

7. The flatulence-supplementing lithium positive electrode sheet according to claim 6, characterized in that: The active coating comprises an active substance, a conductive agent and a binder; the active substance is one of lithium cobalt oxide, lithium-rich lithium manganese oxide, nickel cobalt lithium manganese oxide, lithium manganese oxide and lithium iron manganese phosphate; the conductive agent is one of superconducting carbon black, carbon nanotubes and carbon fibers; the binder is one of polytetrafluoroethylene, polyvinylidene fluoride and polyacrylic acid amide; the conductive binder in the functional coating is a polyimide-carbon nanotube composite conductive binder ZONE80.

8. The flatulence-supplementing lithium positive electrode sheet according to claim 6, characterized in that: The current collector is conventional aluminum foil, composite aluminum foil or perforated aluminum foil.

9. The flatulence-supplementing lithium positive electrode sheet according to claim 6, characterized in that: The active material accounts for 92% to 96% of the total solid mass of the active material, the conductive agent and the binder, and the surface density of the active coating is 100 to 280 g / m 2 The lithium-supplementing composite additive accounts for 90wt% to 95wt% of the functional coating, and the surface density of the functional coating is 3 to 23g / m 2 .

10. Use of the lithium-supplementing composite additive according to any one of claims 1 to 5 or the lithium-supplementing positive electrode sheet for inhibiting flatulence according to any one of claims 6 to 8 in a lithium battery, characterized in that: The lithium battery structure also includes a negative electrode plate, a separator and an electrolyte.

Citation Information

Cited By

  • High-temperature-resistant lithium-supplementing positive electrode material and preparation method thereof

    CN120221657A

  • Secondary battery and electric device

    CN122338178A

  • A secondary battery and an electric device

    CN122338178B